THE RELATIONSHIP OF LONG TIME SUFFERING FROM TYPE 2 DIABETES MELLITUS ON THE DEGREE OF PERIPHERAL NEUROPATHY AT GOTONG ROYONG HOSPITAL, SURABAYA - Kamilah, Hurriyatul; Muliono, Ari Christy; Anggriani, Tabita Novita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Peripheral neuropathy is one of the most frequent complications in Diabetes Mellitus. The prevalence of diabetic neuropathy based on studies is 8% in newly diagnosed DM sufferers and 50% in patients who have long suffered from DM. Peripheral neuropathy is defined as damage to the peripheral nerves which can cause damage to sensory, motor and autonomic nerve function.Objective: This study aims to determine the relationship between the duration of suffering from Type 2 Diabetes Mellitus and the degree of peripheral neuropathy at the Gotong Royong Hospital in Surabaya.Method: This research is an observational analytical study with a cross-sectional design using an instrument in the form of a questionnaire on type 2 DM patients at the Gotong Royong Hospital in Surabaya from August to October 2023. The number of samples used in the research was 45 people.Results: The results of the analysis of the relationship between the duration of suffering from Type 2 Diabetes Mellitus and the degree of peripheral neuropathy using the Spearmen's test showed p = 0.023.Conclusion: There is a significant relationship between the duration of suffering from Type 2 Diabetes Mellitus and the degree of peripheral neuropathy at the Gotong Royong Hospital in Surabaya.